Assessing Preoperative Risk Factors With Sex Disparities in Total Joint Arthroplasty Patients and Financial Outcomes From the National Inpatient Sample Database. Issue 21 (1st November 2020) - Cheah, Cheryl; Hussein, Inaya Hajj; El Othmani, Amjad; Rizvi, Syed A.; Sayeed, Zain; El-Othmani, Mouhanad M.
Abstract : Introduction: Disparities in the healthcare system imply potential risks for vulnerable groups whose needs are not appropriately met. Total joint arthroplasty (TJA) is successful in treating end-stage arthritis, resulting in increased demand for the procedure, however remains underused in both sexes, especially in women. Although multiple studies assessed the differences in postoperative morbidities between sexes, there remains a lack in understanding patients' preoperative clinical profile and nonclinical demographics. The aim of this study is to provide a population-based epidemiologic assessment of preoperative risk factors and sex disparities and assess differences in outcomes following TJA. Methods: The National Inpatient Sample database from 2006 to 2011 was analyzed. Patients who underwent primary total knee and hip arthroplasty were identified and stratified into two cohorts of male and female, and demographic data and comorbidities were collected. Postoperative complications, length of stay, total charges, and discharge destination were measured for matched cohorts. Results: Female patients present for TJAs at an older average age, are less likely to present with AIDS, alcohol abuse, coagulopathy, congestive heart failure, drug abuse, liver disease, peripheral vascular disease, and renal failure, and are more likely to present with anemia, autoimmune disorders, chronic obstructive pulmonary disease, depression, obesity, and valvular disease. Postoperatively, the average length of stay for female patients was markedly higher (3.52 versus 3.39) and a lower percentage went home (59% versus 73%). Overall, female patients experience greater odds of any complication while in-patient. Discussion: This study highlighted sex differences in areas that could account for the underuse of the procedure in both sexes, with women affected to a greater extent. Understanding these factors will help address the unmet needs of both sexes after TJA by encouraging future studies and provider education to ensure that all patients are able to access the necessary procedures for pain relief and functional improvement.